Lipid-based nanoparticles for altering immune response: A step towards targeted cancer immunotherapy - Ismail, Noha Samir (AUC Knowledge Fountain, 2015)
Since cancer is an extremely heterogeneous disease of origin, scientists are always trying to define novel approaches that can eliminate this disease. Over decades now, surgery, radiotherapy and chemotherapy have been the conventional methods to eradicate cancer. Unfortunately, cancer resistance has developed, in which tumor cells became resistant to the majority of chemotherapeutics. Consequently, people started to use combination therapy as a more intensified protocol to counteract the aggressiveness of cancer. However, the results are not satisfactory till now and lots of optimizations are needed in order to make sure that synergistic not antagonistic effects are happening. That is why scientists started to revisit cancer immunotherapy field after long years of its discovery. They are trying to understand more about the manifestations that occur in case of tumor induced immunosuppression. They are rapidly defining new approaches for harnessing the immune system against cancer. Different methodologies are developed in the last ten years, yet optimizations are still in process. The significant hurdle in the field of cancer immunotherapy is the selectivity towards certain immune cell population. In other words, how selective targeting could be achieved with high affinity to the cell of interest. That led to the evolution of cancer nano-immunotherapy where nanoparticles are engineered in a certain manner that can elicit a selective interaction with the target receptor. Many studies have revealed how nanotechnology is a promising tool in harnessing immune system against cancer. However, targeting as a technique is still paving the way for the optimum particle-cell interaction. In the current study, we are paving the way to target immune cells infiltrating the tumor. The challenge here is that the population of cancer cells themselves are much more than the immune cells. In this study, the response of different immune cell lines towards internalization of different surface charged lipid-based nanoparticles (NPs) was investigated at different time frames. The hypothesis is whether specific immune cell line isolated from melanoma tumor model and lymphoid organ like spleen could be targeted with liposomes having different surface charges, could this be considered a novel approach for targeting immune cells passively depending only on surface charge. In the first part, three sets of fluorescently labelled nano-liposomes were engineered as a model for different surface charges, the cationic DOTAP NP, anionic DOPG NP and near neutral DOPC NP with mean diameter of 220, 190, 210 nm and Zeta Potential of +36, -48 and -17.4 mV respectively. Physical stability of the NPs was evaluated by monitoring the changes in size and zeta potential. B16 melanoma cancer model was induced subcutaneously in C57BL/6 black mice (10 weeks age), divided into four groups each of five mice. CD11c Dendritic Cells (DCs), CD11b macrophages, CD90.2 T-cells and CD49b Natural Killer (NK) cells were isolated from the tumors and spleens of each group. The three sets of NPs were tested against the isolated cell lines. The cellular uptake (internalization) was assessed by normalizing the fluorescence of the cells against their protein concentration, then all samples were acquired to flow cytometry, and shifts in fluorescence histograms on horizontal axis were monitored against PE channel on the vertical axis. Results reveal the presence of preferential internalization of specific surface charge over others in some cell lines in different time frames. For the first time differences in the internalization pattern are reported in the same immune cell line isolated from two different contexts tumor and spleen. These results might serve as a guideline for a rational design of successful nano-carriers that can maximize the targeting, and hence the therapeutic efficacy towards certain population of immune cells. In the second part and in the sense of screening the different pathways that contribute to immunosuppression, STAT3 (Signal Transducer and Activator of Transcription 3) pathway is considered one of the promising targets that when inhibited will reverse the immunosuppressed status of DCs. The molecular STAT3 inhibitor is investigated for the first time for its ability to offer superior properties in terms of specificity of STAT3 without affecting the other STATs and eliciting immunomodulatory effect. Pegylated nano-liposomes were synthesized with size of 190 nm loaded with conjugated form of the drug which is drug-cholesterol in order to maximize the loading efficiency reaching 82Â±4% and physical stability with minimal changes in size and zeta potential. Cryo-TEM revealed the formation of predominant unilamillar structures. The efficacy of conjugated drug-NP was evaluated in-vitro on different cells: Bone Marrow derived DCs (BMDCs), DC cell line, B16F10, 4T1 and MDA-MB-231. The BMDCs primary cultures were generated from bone marrow of C57BL/6 mice femurs. The purity of CD11c lineage of BMDCs was assessed by flow cytometry and showed 70-80% purity. In order to mimic the tumor microenvironment surrounding DCs in the tumor i.e. induce immunosuppression and downregulation of DCs surface receptors, high levels of phospho-STAT3 (pSTAT3) were induced via conditioning DCs with different conditioning media of B16, LLC, and 4T1. It has been revealed that B16 conditioning media induced the highest amount of pSTAT3 based on western blot, flow cytometry and cytokine analysis. DCs by then showed downregulation of CD80, CD86 and major histocompatibility complex class II (MHCII). Finally, the drug-NP and free drug (5Âµmole) were added to the immunosuppressed DCs for 24hrs and maturation status was assessed using flow cytometry. Expression of CD86, MHCII and CD80 were evaluated after gating CD11c double positive population. No significant change was observed in case of CD80. Slight increase was observed in case of CD86. However, surprisingly there was a dramatic increase in MHCII with 3 folds higher expression in case of free drug and 1.3 fold with drug-NP in only 24 hrs, this reflects sustained release of the drug from the NP. These results demonstrate the potential of the STAT3 inhibitor in reversing the immunosuppressed status of DCs in tumor microenvironment and its immunomodulatory role for the first time.